Pemilihan Internet Service Provider WiFi dengan Metode MADM-SAW (studi kasus Kecamatan Medan Marelan) - Manik, Charla Tri Selda; Handasah Pohan, Ummu; Widasari Sitopu, Mutiara; Habibi Daulay, M. Sukri; Pardede, Morlan (Politeknik Penerbangan Surabaya, 2024)
Internet access has become a major need for various groups, including individuals, businesses, and governments. Choosing the right Internet Service Provider (ISP) is very important to ensure the quality and smooth access of the internet. Ideally, the choice of ISP is not only based on price or popularity, but also on technical aspects such as connection speed, network stability, as well as customer service and technical support. A reliable and quality ISP ensures a fast and stable internet connection, which is essential for daily online activities. This study provides a reference for Wi-Fi internet service providers (ISP) that are most suitable for use in the Medan Marelan sub-district area, Medan City using the MADM-SAW method. The result are My Republic is in first place, BizNet in second, Iconnet in third and in last place is Indihome.